The role of information technology in STEM education - Nguyen, Trung Chi; Nguyen, Thang Chien; Nguyen, Hau Bui (Asian Journal of Education and Training, 2024)
The ubiquity of IT (Information technology) for teaching at large is a reality that can be observed, including STEM education, which is the field of study of this research. In view of this situation, this work is intended to determine the role of IT in STEM (Science, Technology, Engineering, Mathematics) education. It was decided to conduct a systematic review based on PRISMA model and adding information obtained from the analysis of fugitive literature. The literature review was carried out on a total of 16 articles. The main inclusion criteria were a temporal selection from 2015 to March 2023, the inclusion of the terms IT and STEM in the title, abstract or keywords of the articles. The main results show an increasing tendency of this topic, especially in English research. Most relevant conclusions of the systematic review evidence a positive relationship between IT and STEM education, although some negative aspects are also highlighted as there is still a lack of resources and teacher training, leading to ineffective application of IT in STEM classes. The research results have important practical implications, it motivates teachers to research, propose and implement measures to enhance the role of IT in STEM education, while minimizing the limitations that have been identified.